KEBIJAKAN DAN POLITIK INTEGRASI IMIGRAN DI PRANCIS - Wahyuddin Yudi; Irianti Bandu; M. Hasyim (JURNAL ILMU BUDAYA, 2021)
This study aimed at discussing the immigration in France by focusing on two aspects, namely the politic and the identity. The first concerns about the policy of the French government toward the immigration in the course of history. The second aspect discusses how the government imposes the politic of “assimilation” of the migrant’s identity as an effort to integrate their society. It means that the immigrants are asked to behave as the “French native” particularly in the public space. Collecting data are carried by field research; observation, interview and literature studies. While for analyzing the data, it is used the interpretative method.